Carbon stocks in the mud areas of the Chinese marginal seas - Ma, Haili; Xiao, Xiaotong; Ding, Yang; Feng, Xuwen; Chen, Weifang; Sun, Liguang; Bao, Xiaohan; Duan, Shanshan; Zhao, Meixun (Frontiers in Marine Science, 2023)
Continental marginal seas are key systems in the global carbon cycle. Carbon stocks represent the ability to store carbon, thus quantifying the carbon stocks in marine sediments would help to better understand their importance in the carbon cycle. In this study, 17 sediment cores in the mud areas of the South Yellow Sea and the East China Sea were measured for total organic carbon (TOC) and its stable isotope (δ13C), and dry bulk density; and from which the carbon stocks and carbon stock accumulation rate as well as marine/terrestrial carbon stocks/carbon stock accumulation rate were calculated. The carbon stocks in the mud area of the South Yellow Sea showed a decreasing trend during 1855 to 1950 caused by the relocation of the Yellow River Estuary in 1855, but increased after 1950s due to increased sediment input via the enhancement of South Shandong Coastal Current. In the Min-Zhe belt of the East China Sea, carbon stocks showed an overall high marine proportion due to the phytoplankton bloom induced by high nutrient level, but the decreased carbon stocks in recent decades were mainly caused by the construction of reservoirs in the Yangtze River that reduced sediment transports. The average carbon stocks in 1 m sediments from the South Yellow Sea (45.2 t ha-1) and Min-Zhe belt (52.8 t ha-1) were low compared to that of global marine sediments (66.6 t ha-1), while the carbon stock accumulation rate showed much higher values (0.1 t ha-1 yr-1 in South Yellow Sea and 0.31 t ha-1 yr-1 in the Min-Zhe belt) because of higher sedimentation rates. Although carbon stocks of Chinese marginal seas were also lower than that of the tidal flats (70.7 t ha-1) and wetland (123.6 t ha-1) in China, their much larger area could store 0.75 Pg C in marine sediments. Our temporal records suggest that anthropogenic activities have reduced carbon stocks in the marginal seas since 1950, causing carbon to re-enter the atmosphere to impact climate changes.